Rock Melon Activated Carbon (RMAC) for Removal of Cd(II), Ni(II) and Cu(II) from Wastewater: Kinetics and Adsorption Equilibrium - Said, N.; Amalina, Roslan; Mazza Seddiq, A. Abbakar; Syafiqah , A. Khairuddin; Hajar Atirah, M. Sukri (IACSIT Press, 2015)
The use of effective adsorbents has been investigating as a replacement of current costly methods for heavy metals removal. The present work evaluates the potential of rock melon shell waste as alternative adsorbent for cadmium, nickel and copper ions in aqueous solution. The rock melon shells were dried, ground and separated based on the sizes through sieve shaker. Then, the rock melon shell powder was activated at temperature range of 400 ˚C - 650 ˚C. FESEM and BET were used for adsorbent morphology and surface area analysis. The prepared adsorbent and adsorbate were applied for testing and manipulating the process parameter effects. The results were analyzed by using the Atomic Absorption Spectroscopy (AAS). The optimal process conditions were used for adsorption equilibrium and kinetics justification. The removal of the heavy metals improved as the pH, contact time and adsorbent dosage increased. However, it tended to achieve equilibrium state once the active sites of the adsorbent were fully occupied. The highest removal of Cd(II), Ni(II) and Cu(II) ions equilibrated within 120 min, at pH of 8 and adsorbent dosage was 0.3 g which was exceed 99%. The second order kinetics model best fits the obtained data while the mecahanism indicates surface adsorption and intraparticle diffusion. The adsorption equilibrium accompanies the Freundlich isotherm for cadmium and nickel, but the Langmuir for copper ion.